2005
DOI: 10.1108/02634500510589958
|View full text |Cite
|
Sign up to set email alerts
|

Shoppers' satisfaction levels are not the only key to store loyalty

Abstract: In this research study, grocery shoppers were interviewed to identify the factors that influence satisfaction with their primary store and the factors that encourage them to continue patronising this store despite being presented with an inducement to shop at another store. The study estimated two models; one predicting store satisfaction and the other predicting store loyalty. The results demonstrate that the significant factors that contribute to store satisfaction have little in common with the factors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 30 publications
4
62
0
6
Order By: Relevance
“…This concurs with Sivadas and Baker-Prewitt [2000] and Miranda, Konya and Havrila [2005], among others, who have shown that favourable evaluations of the shopping experience do not necessarily result in loyalty and repatronage, suggesting that other factors are involved in patronage choices. Due to their propensity to be decisive and saving time in shopping, men appear to show more loyalty in their shopping choices.…”
Section: Resultssupporting
confidence: 90%
“…This concurs with Sivadas and Baker-Prewitt [2000] and Miranda, Konya and Havrila [2005], among others, who have shown that favourable evaluations of the shopping experience do not necessarily result in loyalty and repatronage, suggesting that other factors are involved in patronage choices. Due to their propensity to be decisive and saving time in shopping, men appear to show more loyalty in their shopping choices.…”
Section: Resultssupporting
confidence: 90%
“…However, malls at times fail to recognise that what infl uences buyers ' satisfaction is not the same as what engenders store loyalty (of tenants), and consequently do not effectively develop the shopping ambience to stimulate buying decisions. Hence, they need to vigilantly manage the quality of arousal by developing adequate customer involvement in the buying process of retail shoppers ( Miranda et al , 2005 ). Considering the evidence from the previous studies discussed above, Hypothesis 2b is framed as follows:…”
Section: Ambience and Shopping Arousalmentioning
confidence: 99%
“…As higher stimulation or interactive learning provided by the retailers focuses on gaining initial experience on the product use, consumers tend to engage in higher arousing activities by acquiring the product ( Menon and Kahn, 2002 ). Hence, they need to vigilantly manage the quality of arousal by developing adequate customer involvement in the buying process and retail shoppers ( Miranda et al , 2005 ). Therefore, hypothesis may be stated as:…”
Section: Ambience Beliefs and Shopping Arousalmentioning
confidence: 99%